In vitro pharmacoregulation of CC chemokine ligand 5 and its receptor CCR5 in diffuse lung diseases - Veronika Sekerova; Daniela Subrtova; Frantisek Mrazek; Agata Gibejova; Vitezslav Kolek; Roland M. du Bois; Martin Petrek (Hindawi Limited, 2003)
Background: CC chemokine ligand (CCL)5 and its receptor CCR5 contribute to leukocyte migration into lungs of patients with diffuse lung diseases (DLD). Pharmacological regulation of CCL5 and CCR5 expression was therefore explored in bronchoalveolar cells obtained from patients with DLD.